PENERAPAN OUTDOOR LEARNING MELALUI IDENTIFIKASI KECERDASAN NATURALISTIK KEPADA SISWA KELAS V DI SDN PONDOK CABE ILIR 01 - Firsya Fimela Azzahra; Apri Utami Parta Santi, Azmi Al Bahij (CV. ADIBA AISHA AMIRA, 2025)
Naturalistic intelligence plays a crucial role in fostering students’ environmental awareness. However, classroom-based learning often emphasizes theory without providing direct experiences that enhance conceptual understanding. This study uses a qualitative descriptive approach to examine how outdoor learning is implemented to develop the naturalistic intelligence of fifth-grade students at SDN Pondok Cabe Ilir 01. Various activities such as ecosystem observation, photosynthesis exploration, and art using natural materials were conducted to support contextual and meaningful learning. The findings indicate that direct interaction with nature helps students develop curiosity, environmental sensitivity, and critical thinking. Despite facing challenges such as limited facilities and maintaining student focus during outdoor activities, teachers played an essential role in guiding students and designing balanced learning experiences. These findings align with Palupi (2024), who emphasized the importance of strategic planning in implementing effective outdoor learning models.